Crashworthiness and optimization of bionic sandwich cores under out-of-plane compression - Zhou, Jianfei (2023)
In this paper, novel bionic sandwich cores are proposed based on the cross section of seagull feather shaft to provide an effective protective mechanism against impact. The relative density of the bionic core is firstly defined, which is closely related to cell configuration and geometric parameters. Through finite element simulations supported by experiments using 3D printed specimens, the novel bionic core is found to be superior in crashworthiness as compared to conventional honeycomb core in terms of specific energy absorption and mean force under out-of-plane compression. To decipher the underlying mechanisms for the enhanced performances, a theoretical model for the bionic core is derived based on the simplified super folding element (SSFE) theory. The effects of wall thickness, number of cells and amplitude of sinusoidal beam on relative density and crashworthiness are explored. It is revealed that the increase in wall thickness and number of cells led to improvements of load bearing capacity. An optimal structure is subsequently obtained based on the complex proportional assessment (COPRAS) and response surface method (RSM). Compared to conventional honeycomb core, the optimal peak force of the bionic core is decreased by 11.53%. Through the combination of experiment, simulation and theoretical analysis, this study provides a novel idea for the optimization of the crashworthiness of the bionic core under out-of-plane compression.